Does investment in palm oil trade alleviate smallholders from poverty in Africa? Investigating profitability from a biodiversity hotspot, Cameroon - Ayompe, L.M.; Nkongho, R.N.; Masso, C.; Egoh, B.N. (Public Library of Science, 2021)
In this study we investigate whether the increasing investment in smallholder oil palm plantations that contributes to deforestation is motivated by financial gains or other factors. We evaluate the financial viability of smallholder farmers selling fresh fruit bunches (FFBs) to intermediaries or agro-industrial companies with mills, or processing the FFBs in artisanal mills to produce palm oil. We use data collected in four oil palm production basins in Cameroon and carried out a life cycle assessment of oil palm cultivation and CPO production to understand financial gains. We use payback period (PBP), internal rate of return (IRR), benefit cost ratio (BCR) and net present value (NPV) for 1 ha of oil palm plantation over 28 years at a base discount rate of 8% to asses viability. Our results show that smallholders make more money processing their FFBs in artisanal mills to produce CPO than selling FFBs to intermediaries or agro-industrial companies with mills. The sensitivity analysis show that land ownership is the single most important parameter in the profitability of investment in palm oil cultivation and trade. In addition to land cost, smallholders suffer from borrowing at high interest rates, high field management costs, while recording low on-farm FFB/processing yields. To improve the financial viability of smallholders investing in oil palm cultivation, measures are needed to encourage them to access land, get loans at reduced interest rates, reduce the cost of field management, adopt good agricultural practices to improve on-farm FFB/processing yields, as well as to generate additional revenue from the sale of other products.